LPV Model-based Adaptive MPC of an eVTOL Aircraft During Tilt Transition Subject to Motor Failure - Qu, Shen; Zhu, Guoming; Su, Weihua; Swei, Sean Shan-Min (International journal of control, automation, and systems, 2023)
This paper applies novel LPV (linear parameter-varying) model and MPC (model predictive control) methods to a tilt-transition process with rotor failure for electric vertical take-off and landing aircraft of six distributed electric rotors with a fixed-wing for level flight, where two rotors are tiltable to generate variable thrust vector during the tilt-transition from hovering to steady-state level flight and the rest of four cannot be tilted. During the level flight, the aerodynamic lift induced by fixed wing maintains flight altitude. Based on a predefined nominal tilting trajectory scheduled by tilt-rotor angular position and the failed rotor speed, a discrete-time LPV model is constructed based on significantly reduced number of linear time invariant models obtained by linearizing the nonlinear eVTOL aircraft model along the tilting trajectory, where tilt-rotor angle and failed rotor speed can be measured in real-time. An LPV modeling error evaluation method is proposed based on the σ shifted ℌ 2 norm, and adaptive model predictive controller is designed with the dynamic reference compensation. Simulation study indicated the success of the adaptive MPC strategy based on tilt-transition LPV model with rotor failure.